Management of pouch neoplasia: consensus guidelines from the International Ileal Pouch Consortium. (September 2022) - Kiran, Ravi P; Kochhar, Gursimran S; Kariv, Revital; Rex, Douglas K; Sugita, Akira; Rubin, David T; Navaneethan, Udayakumar; Hull, Tracy L; Ko, Huaibin Mabel; Liu, Xiuli; Kachnic, Lisa A; Strong, Scott; et al.
Summary: Surveillance pouchoscopy is recommended for patients with restorative proctocolectomy with ileal pouch–anal anastomosis in ulcerative colitis or familial adenomatous polyposis, with the surveillance interval depending on the risk of neoplasia. Neoplasia in patients with ileal pouches mainly have a glandular source and less often are of squamous cell origin. Various grades of neoplasia can occur in the prepouch ileum, pouch body, rectal cuff, anal transition zone, anus, or perianal skin. The main treatment modalities are endoscopic polypectomy, endoscopic ablation, endoscopic mucosal resection, endoscopic submucosal dissection, surgical local excision, surgical circumferential resection and re-anastomosis, and pouch excision. The choice of the treatment modality is determined by the grade, location, size, and features of neoplastic lesions, along with patients' risk of neoplasia and comorbidities, and local endoscopic and surgical expertise.